SOCIAL NETWORKS AND STAKEHOLDER PARTICIPATION IN THE COMPREHENSIVE RURAL DEVELOPMENT PROGRAMME IN LIMPOPO PROVINCE, SOUTH AFRICA - Olusegun Samson Obadire; Mukondelela John Mudau; Jethro Zuwarimwe (European Scientific Journal, ESJ, 2014)
A critical goal of the Comprehensive rural development programme (CRDP) is to stimulate agricultural production for the sector to contribute to food security and addressing skewed patterns of land distribution through rights-based interventions.This study investigated the factors that influence the stakeholders’ participation in the CRDP in South Africa using social network analysis.A simple random sampling technique was used to select 300 respondents from the various CRDP projects and 36 respondents were purposively selected for focus group discussion used for the study. Data was collected using questionnaire and focus group discussion guide. The mean age for the respondents was 35.5 years while the mean income level of the respondents was R1000. This study revealed that participation is high in benefit sharing (PI=0.6) but low in other key areasof study. Participation in Council of stakeholders interaction had the least (PI=0.1). The majority of the respondents (83%) agreed that the existence of the CRDP projects had improved the quality of life and livelihood of the people and 72% agreed the projects had alleviated poverty among the people in the community.The result revealed increasing economic activities, crime reduction, clinic providing health services, increase in the size of local workforce, providing local access to education and training, provision of free internet and computer access as being associated with the CRDP projects.The CRDP projects, though was achieving some of its objectives but sustainability issues as well as low youth participationremains a challenge.